(untitled) (Research, Society and Development, 2020)
The research aims to analyze the motivational aspects that influence the practice of capoeira in the municipality of Crato-CE. This is a survey, with a quantitative approach and exploratory level, carried out from January to July 2017, with members of 09 capoeira groups in the municipality of Crato-CE. 65 capoeiristas with ages between 15 and 36 years old participated in the research, of which 49 are male and 16 female. For data collection we used the Scale of Reasons for Sports Practice (EMPE). It was found that the dimension of health motivation obtained higher averages and prominence among those investigated, followed by technique, affiliation, physical conditioning and in less expressiveness, energy, context and status. It is concluded that, the motivation of greater influence for the practice of capoeira consisted of the health aspect, being this motivation of great relevance for improving the quality of life of capoeiristas, considering that capoeira can help in the physical, mental, cognitive and of its practitioners.